2015
DOI: 10.3945/ajcn.114.094920
|View full text |Cite
|
Sign up to set email alerts
|

First-trimester plasma tocopherols are associated with risk of miscarriage in rural Bangladesh

Abstract: In pregnant women in rural Bangladesh, low plasma α-tocopherol was associated with increased risk of miscarriage, and low γ-tocopherol was associated with decreased risk of miscarriage. Maternal vitamin E status in the first trimester may influence risk of early pregnancy loss. The JiVitA-1 study, from which data for this report were derived, was registered at clinicaltrials.gov as NCT00198822.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 40 publications
4
54
1
Order By: Relevance
“…It was stated that there is evidence in pregnant women that shows a significantly increased rate of miscarriage with a vitamin E concentration < 12 μmol/L (Shamim et al, 2015), which corresponds to the concentration at which an increased risk of haemolysis was observed by Horwitt (1960). It was suggested that DRVs should be set using serum vitamin E concentration as a biomarker, taking into account the negative impact on health of concentrations < 12 μmol/L.…”
Section: Outcome Of a Public Consultation On A Draft Scientific Opinimentioning
confidence: 99%
See 4 more Smart Citations
“…It was stated that there is evidence in pregnant women that shows a significantly increased rate of miscarriage with a vitamin E concentration < 12 μmol/L (Shamim et al, 2015), which corresponds to the concentration at which an increased risk of haemolysis was observed by Horwitt (1960). It was suggested that DRVs should be set using serum vitamin E concentration as a biomarker, taking into account the negative impact on health of concentrations < 12 μmol/L.…”
Section: Outcome Of a Public Consultation On A Draft Scientific Opinimentioning
confidence: 99%
“…The Panel also notes that plasma α-tocopherol concentrations of these pregnant women were lower than mean maternal concentrations in Western countries such as the US and Ireland, i.e., respectively, 31.3 µmol/L at delivery (Pressman et al, 2003) and 20.6 µmol/L at 10-20 weeks of gestation (Kiely et al, 1999) (Section 5.2. of the Scientific Opinion). The Panel considers that the study by Shamim et al (2015) cannot be used to derive DRVs for α-tocopherol in pregnant women in the EU.…”
Section: Panel Consideration Of Comments Receivedmentioning
confidence: 99%
See 3 more Smart Citations